Production efficiencies of U.S. electric generation plants: effects of data aggregation and greenhouse gas and renewable energy policy - Lynes, Melissa Kate (Kansas State University, 2015)
Over the last few decades there has been a shift in electricity production in the U.S. Renewable energy sources are becoming more widely used. In addition, electric generation plants that use coal inputs are more heavily regulated than a couple decades ago. This shift in electricity production was brought on by changes in federal policy – a desire for electricity produced in the U.S. which led to policies being adopted that encourage the use of renewable energy. The change in production practices due to policies may have led to changes in the productivity of electric generation plants. Multiple studies have examined the most efficient electric generation plants using the data envelopment analysis (DEA) approach. This study builds on past research to answer three questions: 1) Does the level of aggregation of fuel input variables affect the plant efficiency scores and how does the efficiency of renewable energy input compare to nonrenewable energy inputs; 2) Are policies geared toward directly or indirectly reducing greenhouse gas emissions affecting the production efficiencies of greenhouse gas emitting electric generation plants; and 3) Do renewable energy policies and the use of intermittent energy sources (i.e. wind and solar) affect the productivity growth of electric generation plants. All three analysis, presented in three essays, use U.S. plant level data obtained from the Energy Information Administration to answer these questions. The first two essays use DEA to determine the pure technical, overall technical, and scale efficiencies of electric generation plants. The third essay uses DEA within the Malmquist index to assess the change in productivity over time. Results indicate that the level of aggregation does matter particularly for scale efficiency. This implies that valuable information is likely lost when fuel inputs are aggregated together. Policies directly focused on reducing greenhouse gas emissions may improve the production efficiencies of greenhouse gas emitting electric generation plants. However, renewable energy policies do not have an effect on productivity growth. Renewable energy inputs are found to be as efficient if not more efficient than traditional energy sources.
Keywords: Production efficiencies; Electric utility plants; Renewable energy policies; Energy Economics; Economics (0501); Economics, Agricultural (0503); Environmental economics (0438)